Optimisation of a Composite Material Automotive Driveshaft by Using FEM (International Journal of Current Engineering and Technology, 2015)
In an automobile industry a drive shaft play a major role in power transmission and it is generally is made of conventional metallic structure is replace by composite structure because they have higher strength and higher specific stiffness ,as we used Kevlar or Carbon epoxy it having some drawback. In this paper work are deals with the replacement of conventional composite material drive shaft with a E-glass carbon /Epoxy, High strength carbon/ Epoxy and High module carbon /Epoxy to overcome the drawback of conventional composite material drive shaft. In this paper we are work for suggesting the best composite material for drive shaft and improve the life of drive shaft and also saving the percentage of material.
Keywords: Drive shaft; Composite material; ANSYS11.0; Material Saving